Implikasi Hukum Alasan Efisiensi Pekerja: Studi Kasus PHK PT Fast Food Indonesia Tahun 2025 - Junika Gabriella Cecille Hutapea; Gunardie Lie (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
Termination of Employment (PHK) for efficiency reasons is a highly relevant topic in labor law discussions, especially following the enactment of the Job Creation Law (Law No. 11 of 2020). Efficiency-based PHK is often linked to companies’ efforts to adjust their operations in response to economic challenges, such as reduced purchasing power following the COVID-19 pandemic. However, practices of unilateral PHK, lacking sufficient evidence and not adhering to the prescribed legal procedures, raise serious concerns about the legitimacy and fairness of such policies. This research aims to examine the application of the efficiency principle in PHK at PT Fast Food Indonesia (KFC Indonesia) and compare the legal guarantees of workers’ rights before and after the enactment of the Job Creation Law. The research methodology used is a normative approach, analyzing relevant legal provisions and comparing them with industrial relations practices in the field. The findings reveal that although efficiency is recognized by law as a valid reason for PHK, its application is often not accompanied by sufficient objective evidence or the mandatory bipartite procedures. This creates an imbalance between the interests of the company and the protection of workers' rights. Furthermore, the implementation of the Job Creation Law provides greater flexibility for employers to carry out PHK, yet it reduces certainty in the protection of workers affected by such decisions